ELABELA promotes the migration and homing of bone marrow mesenchymal stem cells to myocardial injury sites through the ERK1/2/miR-299a-5p/Exo70 pathway - Hou, Jing-Yu; Wu, Hao; Li, Shuang-Mei; Li, Xiao-Jing; Yang, Shu-Jun; Chen, Xu-Xiang; Zhou, Chang-Qing; Long, Hui-Bao; Wu, Hai-Dong; Fu, Jia-Ying; Guo, Ya-Jie; Wang, Tong (Frontiers in Pharmacology, 2025)
BackgroundBone marrow mesenchymal stem cells (BMSCs) hold promise for repairing myocardial injury following acute myocardial infarction (AMI), but their clinical application is hindered by poor migration, homing efficiency, and survival rates. Previously, we demonstrated that ELABELA (ELA), a small peptide, enhances the survival of rat BMSCs under hypoxia-reoxygenation (H/R) conditions by activating ERK1/2. However, the role of ELA in promoting BMSCs migration and homing to injured cardiomyocytes remains unclear.MethodsPrimary BMSCs and neonatal rat ventricular myocytes (NRVMs) were isolated and cultured. NRVMs were exposed to H/R to mimic the microenvironment of AMI in vitro. The migration of BMSCs toward the injured myocardium was assessed in different treatment groups using transwell and chemotaxis assays. Additionally, in vivo studies were performed using a rat myocardial infarction/reperfusion injury (MI/RI) model with DIR-labeled BMSCs. Cardiac repair was evaluated through fluorescence imaging, echocardiography, and histological analysis. Transcriptome sequencing and bioinformatics analysis were employed to identify and validate the mechanisms by which ELA promoted the migration of BMSCs. A dual luciferase assay was used to investigate the interaction between Exo70 and miR-299a-5p. Subsequently, a series of experimental procedures were performed, including sequential silencing of APJ or Exo70, overexpression of miR-299a-5p, inhibition of ERK1/2 phosphorylation, assessment of BMSCs migration through transwell and scratch assays, detection of F-actin polymerization via immunofluorescence, and evaluation of the expression levels of each factor using qPCR and Western blotting.ResultsIn vitro, the migration ability of ELA-pretreated BMSCs was significantly augmented in the H/R environment. ELA pretreatment effectively heightened the homing capacity of BMSCs to the site of myocardial injury and their proficiency in repairing myocardial damage in vivo. Transcriptome sequencing revealed upregulation of Exo70 in ELA pretreated BMSCs, which promoted F-actin polymerization and migration. Overexpression of miR-299a-5p reduced Exo70 expression and impaired BMSCs migration. ELA also activated ERK1/2 phosphorylation, while inhibition of ERK1/2·with U0126 abrogated F-actin polymerization and migration, increasing miR-299a-5p levels and reducing Exo70.ConclusionELA enhances BMSCs migration and homing to injured cardiomyocytes by activating the APJ receptor, promoting ERK1/2 phosphorylation, downregulating miR-299a-5p, and upregulating Exo70, providing a potential therapeutic strategy for improving stem cell-based cardiac repair.